2022
DOI: 10.3389/fvets.2022.927369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with lysophospholipids on performance, nutrient digestibility, and bacterial communities of beef cattle

Abstract: An experiment was conducted to investigate the influences of supplemental lysophospholipids (LPL) on the growth performance, nutrient digestibility, and fecal bacterial profile, and short-chain fatty acids (SCFAs) of beef cattle. Thirty-six Angus beef cattle [565 ± 10.25 kg body weight (BW)] were grouped by BW and age, and randomly allocated to 1 of 3 treatment groups: (1) control (CON, basal diet); (2) LLPL [CON supplemented with 0.5 g/kg LPL, dry matter (DM) basis]; and (3) HLPL (CON supplemented with 0.75 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Similar to our observations in Exp.1, Zhang et al ( 36 ) reported linear increases in FBW, ADG, and feed efficiency in supplemented Angus cattle without affecting DMI when the dose of a lysophospholipid-derived feed additive was increased from 0.5 to 0.75 g/kg of DM. Moreover, Drago ( 15 ) noted improvements in ADG and feed efficiency in LYSO-supplemented Nellore bullocks submitted to a finishing diet with 7.0% EE but not when the diet contained 3.8% EE.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to our observations in Exp.1, Zhang et al ( 36 ) reported linear increases in FBW, ADG, and feed efficiency in supplemented Angus cattle without affecting DMI when the dose of a lysophospholipid-derived feed additive was increased from 0.5 to 0.75 g/kg of DM. Moreover, Drago ( 15 ) noted improvements in ADG and feed efficiency in LYSO-supplemented Nellore bullocks submitted to a finishing diet with 7.0% EE but not when the diet contained 3.8% EE.…”
Section: Discussionsupporting
confidence: 90%
“…In that study, LYSO did not modify lipid digestion, which suggests that the potential for LYSO to further improve EE digestion was likely decreased when animals are fed rumen-protected highly digestible fat sources. In contrast, Zhang et al ( 36 ) observed a positive linear effect on EE digestion with a lecithin-derived feed additive (up to 8.75 g/animal/day) when rumen-protected fat was added to the diet, but the type and source of fat were not described. The authors suggested that EE digestibility was increased as a result of the effective emulsification of lecithin in reducing the size of fat globules, forming smaller micelles, and, as a consequence, increasing the surface area of lipid droplets for interaction with pancreatic enzymes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Qiu et al [ 25 ] reported that choline, as one of the main components of LPLs, increased the concentration of butyrate in the colon digesta of weaned piglets, which was positively correlated with the body weight of the animals. Therefore, we suspected that the mechanism for LPLs improving ADG might be due to the increased concentration of butyric acid in gut microorganisms, which has also been verified in our previous study [ 26 ]. In a study by Song et al [ 27 ], however, Hanwoo heifers fed a diet with LPLs (0.3% or 0.5% w / w ) did not exhibit altered growth performance.…”
Section: Discussionsupporting
confidence: 58%